“No longer languished in the periphery of existence:” Female bodies, computational-sentiment analysis, and Malay folktales - Wan Nur Madiha Ramlan; Mohd Muzhafar Idrus; Nurul Izzati Hassan (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2025)
Tier 2- Indexed by MyCite